2021
DOI: 10.1021/acs.iecr.1c02838
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Swirl Flow Enhancement Effect on the Particle Drying Process in a Novel Spouted Bed

Abstract: The swirl flow effect was introduced in the spouting bed to change the velocity and volume distribution of the gas phase in different directions, strengthen the radial disturbance, increase the contact area, and optimize the mass transfer, heat transfer, and transmission efficiency of the two-phase flow in the spouted bed. The drying efficiencies of a conventional spouted bed and a spouted bed with an integral swirling blade nozzle (ISBN) under various particle diameters, filling weights, and drying temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Duan et al 38 conducted an experimental study investigating the impact of swirl flow within a spouted bed. The goals were to alter the velocity and volume distribution of the gas phase in various directions, enhance radial disturbances, expand the contact area, and optimize mass transfer, heat transfer, and overall transmission efficiency in a two-phase flow-spouted bed without the use of a draft tube during the drying process.…”
Section: T H Imentioning
confidence: 99%
“…Duan et al 38 conducted an experimental study investigating the impact of swirl flow within a spouted bed. The goals were to alter the velocity and volume distribution of the gas phase in various directions, enhance radial disturbances, expand the contact area, and optimize mass transfer, heat transfer, and overall transmission efficiency in a two-phase flow-spouted bed without the use of a draft tube during the drying process.…”
Section: T H Imentioning
confidence: 99%
“…A spouted bed is a device with stable gas–solid circulation flow pattern, and its applications include mixing, heating/cooling, drying, , coating, and chemical reactions, and the related industries are the chemical and electrochemical, metallurgy, food and agricultural, pharmaceutical, as well as energy and nuclear sectors. Gishler applied spouted bed technology in drying process industry for the first time and reported significantly improved efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It was pointed out that poor hydrodynamics could be induced by porous plates during the drying process. Duan et al 6 evaluated swirl flow effects on the particle drying process in a spouted fluidized bed. It was found that the integral swirling blade nozzle could accelerate the moisture diffusion and enhance the drying rate, which was sensitive to the bed load.…”
Section: Introductionmentioning
confidence: 99%